Discussion Against the Background of Communication Strategies in the Statements of Foreigners Learning Polish as a Foreign Language - Syrek, Małgorzata (Activation – innovation – acculturation. (Glotto)didactics and the migration crisis, 2024)
The article concerns one of the most frequently used communication strategies by foreigners learning Polish. This concept and its connections with communication competences are explained. A study of the frequency of use of the discussion and analysis is presented. The issue was presented against the background of other communication strategies.